The Complexity of the Caspian Basin - Markella, Koutsouradi; John, Karkazis; Petros, Siousiouras; Dionysia, Chondrogianni (European Scientific Journal, ESJ, 2018)
The collapse of the Soviet Union and the emergence of newly independent States marked the uprising of a new era in the region of the Caspian Basin. Failing to reach a consensus regarding the legal nature of the Caspian, Russia, Turkmenistan, Iran, Azerbaijan, and Kazakhstanâ€™s policies have been characterized by a perpetual pursuit of establishing themselves as key-role agents in the region. The question about â€œLake or Seaâ€ is yet to be answered after many decades. This paper focuses on analyzing the significance of the Caspian Basin for the littoral States and how it determines their political agenda.